A retrospective cohort study investigating the association of postcalving intramammary infection and milk yield, somatic cell count, clinical mastitis, and culling risk in first-lactation dairy cows - A. Singh; H. Somula; M. Wieland (Journal of Dairy Science)
ABSTRACT: The objective of this study was to investigate the association of postcalving IMI with milk production and SCC during the first 3 test days after calving, as well as the risk of clinical mastitis occurrence and culling within the first 100 DIM in first-lactation Holstein dairy cows. This retrospective cohort study was conducted at one commercial dairy farm in New York. Postcalving IMI was assessed by means of bacteriological testing of composite milk sample aseptically obtained from all quarters at the day of calving or between 7 and 13 DIM. Data on monthly test-day milk yield and SCC, as well as on the occurrence of clinical mastitis and culling within the first 100 DIM were retrieved from the farm management software. We used generalized linear mixed models to study the associations of postcalving IMI with milk yield and SCC. We found that cows with an IMI with Pasteurella multocida had lower milk yields compared with those without a postcalving IMI, whereas cows with an IMI with Staphylococcus chromogenes had higher milk yields. Similarly, cows infected with Staphylococcus aureus, Staphylococcus chromogenes, Staphylococcus simulans, Streptococcus dysgalactiae, Streptococcus uberis, or Pasteurella multocida had higher SCC compared with their culture-negative herdmates. Logistic regression analyses revealed associations between postcalving IMI and the occurrence of clinical mastitis and culling within the first 100 DIM. Compared with cows without a postcalving IMI, the odds ratio and 95% CI of clinical mastitis were 4.00 (2.76–5.79) for cows with a Streptococcus dysgalactiae IMI, 4.45 (3.16–6.26) for cows with a Streptococcus uberis IMI, and 9.87 (4.88–19.96) for cows with a Pasteurella multocida IMI. Cows identified with an IMI with Staphylococcus aureus, Streptococcus dysgalactiae, Streptococcus uberis, or Pasteurella multocida had higher odds of culling within the first 100 DIM compared with their culture-negative herdmates. The odds ratios (95% CI) were Staphylococcus aureus, 6.36 (4.44–9.13); Streptococcus dysgalactiae, 2.02 (1.42–3.40); Streptococcus uberis, 2.12 (1.40–3.20), and Pasteurella multocida, 2.23 (1.01–4.93). Due to the lack of molecular strain typing of postcalving cultures and those obtained from clinical mastitis cases, we cannot infer a cause-effect relationship. Future research to study the significance and identify possible risk factors of postcalving IMI in first-lactation animals is warranted.